Studying and influence of professional motivation of students when studying graphic disciplines - Abdyrov, Айтжан; Yessekeshova, Марал; Tuleuov, Гульмаржан (Рroblems of engineering and professional education, 2023)
The article presents the results of the study of professional motivation of students in the process of studying graphic disciplines. Questionnaires for the purpose of determining the level of professional motivation and interest in the study of disciplines «Engineering Graphics» specializing in architecture and design. During the experimental studies, it was possible to identify the shortcomings in the teaching of graphic disciplines, which worsen the interest in the study of this discipline. The discipline of engineering graphics is a science that studies the discipline of descriptive geometry and theories of Mechanical Engineering and construction drawings. The achievements of engineering graphics theories are widely used in various fields of technology and science, therefore, for the competent execution of drawings of earthworks, the design and construction of engineering buildings, the basics of the theory of drawing the most necessary buildings to be built on earth, the engineer learns through this theory of engineering graphics. That is why it is so important and necessary to study and study this discipline. Professional motivation affects the professional self-determination of students and their satisfaction with educational and professional activities. It is necessary to form professional motivation in the process of studying not only special, but also professional and practical disciplines, including engineering graphics. To become a highly qualified specialist, in this case, an engineer, a student needs high-quality graphic training. The experience of teachers and researchers shows how important it is to motivate students to study subjects, especially in the early years, when they consider everything related to their future profession as motivational important. The formation of professional motivation of a future specialist is an important direction in the modernization of Education. Keywords: professional motivation, graphic disciplines, engineering graphics, questionnaires, learning efficiency. The article presents the results of the study of professional motivation of students in the process of studying graphic disciplines. Questionnaires for the purpose of determining the level of professional motivation and interest in the study of disciplines «Engineering Graphics» specializing in architecture and design. During the experimental studies, it was possible to identify the shortcomings in the teaching of graphic disciplines, which worsen the interest in the study of this discipline. The discipline of engineering graphics is a science that studies the discipline of descriptive geometry and theories of Mechanical Engineering and construction drawings. The achievements of engineering graphics theories are widely used in various fields of technology and science, therefore, for the competent execution of drawings of earthworks, the design and construction of engineering buildings, the basics of the theory of drawing the most necessary buildings to be built on earth, the engineer learns through this theory of engineering graphics. That is why it is so important and necessary to study and study this discipline. Professional motivation affects the professional self-determination of students and their satisfaction with educational and professional activities. It is necessary to form professional motivation in the process of studying not only special, but also professional and practical disciplines, including engineering graphics. To become a highly qualified specialist, in this case, an engineer, a student needs high-quality graphic training. The experience of teachers and researchers shows how important it is to motivate students to study subjects, especially in the early years, when they consider everything related to their future profession as motivational important. The formation of professional motivation of a future specialist is an important direction in the modernization of Education.